(untitled) - Gunji, Ryoichi (Tokyo, 1971)
This book introduce treatment of deafness (principally perceptive deafness). Medical tratment in general. Location of Hanno-Ryodo-Points and indications of it.
Keywords: Tai mũi họng,Otolaryngology